Admitting students with disabilities. Issue 3 (June 2015) - Unknown
<x xml:space="preserve">Abstract</x> Disability laws prohibit colleges and universities from denying students admission into their programs because of a disability if they are otherwise qualified. Help steer your institution away from legal problems by knowing how the courts and the Office for Civil Rights have ruled in recent cases involving the admission of prospects with disabilities.